Forecasts that missed by a mile. - Lee, Laura (Futurist)
For the past century, almost everyone has been anticipating the year 2000. The writer discusses the predictions that have been proved wrong either because they were too optimistic, too pessimistic, or premature. Sidebars discuss bad predictions that have been made relating to society, commerce, health and medicine, and science and technology, and advice on avoiding making bad predictions is provided.